Raya’s Psychological Individuation in A Space for the Unbound: A Jungian Analysis - Jasmine Putri Fauziyyah; Dwi N C S Kusumaningtyas; Ali Mustofa (New Language Dimensions, 2025)
This research examines the process of self-realization of Raya, the protagonist of “A Space for the Unbound” (2023), through the lens of Carl Jung’s individuation theory. This study focuses on examining the character of Raya and her progression throughout the game as she experiences the individuation process. Using a qualitative-descriptive method rooted in Jungian psychoanalysis, the study examines the integration of four major archetypes: Persona, Shadow, Animus, and the Self. The analytical procedure involves a systematic four-stage approach: participatory data acquisition through full gameplay, narrative-ludic mapping of key conflicts, symbolic interpretation of visual elements, and theoretical synthesis. The findings reveal that Raya’s journey meticulously represents a Jungian individuation process, where the ‘Spacedive’ mechanic functions as a sophisticated interactive metaphor for penetrating the unconscious to confront the Shadow and integrate suppressed childhood trauma. The character’s self-realization is achieved not merely through narrative resolution, but through the transformation of ludic-visual elements—such as environmental shifts and symbolic motifs—that manifest her internal psychological reconciliation. This research concludes that A Space for the Unbound provides a participatory model for understanding trauma recovery, offering significant contributions to both game studies and psychological literary analysis. These insights provide a foundational framework for further studies exploring the intersection of mental health representation and interactive storytelling in digital media.